Hubungan Antara Kecerdasan Naturalis Dengan Hasil Belajar Ilmu Pengetahuan Alam - Avis Mada Aldisa; Tatang Muhajang; Saur M Tampubolon (FKIP UNIVERSITAS PAKUAN, 2015)
The research is quantitative associative research with correlation approach which includes natural intelligence as independent variable and students’ achievement as the dependent variable. The research is aimed at finding out positive correlation between students’ natural intelligence and their achievement on natural science subject. It was done in January 2015. The subjects of the research were students of class VA and VB of SD Negeri Empang. Bogor. The total respondents were 51 students. The data analysis used regression analytical technique and simple correlation which is represented by a regression equation of Y = -47 +0.49x meaning that the correlation is significant. The significance is shown by the correlation coefficient of r xy = 0.967 with determination coefficient of 0.94 or it can be stated that 94% students’ achievement on natural science is influenced by their natural intelligence.